Chronic Post-Concussion Neurocognitive Deficits. II. Relationship with Persistent Symptoms - Maruta, Jun; Spielman, Lisa A.; Yarusi, Brett B.; Wang, Yushi; Silver, Jonathan M.; Ghajar, Jamshid (Frontiers in Human Neuroscience, 2016)
Individuals who sustain a concussion may continue to experience problems long after their injury. However, it has been postulated in the literature that the relationship between a concussive injury and persistent complaints attributed to it is mediated largely by the development of symptoms associated with posttraumatic stress disorder and depression. We sought to characterize cognitive deficits of adult patients who had persistent symptoms after a concussion and determine whether the original injury retains associations with these deficits after accounting for the developed symptoms that overlap with posttraumatic stress disorder and depression. We compared the results of neurocognitive testing from 33 patients of both genders aged 18-55 at three months to five years post-injury with those from 140 control subjects. Statistical comparisons revealed that patients generally produced accurate responses on reaction time-based tests, but with reduced efficiency. On visual tracking, patients increased gaze position error variability following an attention demanding task, an effect that may reflect greater fatigability. When neurocognitive performance was examined in the context of demographic- and symptom-related variables, the original injury retained associations with reduced performance at a statistically significant level. For some patients, reduced cognitive efficiency and fatigability may represent key elements of interference when interacting with the environment, leading to varied paths of recovery after a concussion. Poor recovery may be better understood when these deficits are taken into consideration.